Penerapan Teori Struktur Cerita pada Pembuatan Film - Oscario, Angela (Humaniora, 2011)
Since it was created in 19th century, film has been developed into one important communication media. The successful of communication depends on how the story was told; therefore many story structure theories were created. Unfortunately, those theories are rarely applied. Literature and field studies were performed to delve deeper in story structure theories and their implementations, starts from 3 acts structure, 8 sequences structures, and hero’s journey. Based on observation, these theories have been used in many box office films. Those theories are flexible, not strict formulas more likely the guidance maps to compose story. Structure story theories are the frameworks. But the content in the framework depends on each individual’s creativity. Therefore, using those theories won’t make our story generic. Story structure theories are tools to provoke, encourage, boost, and develop creativity. By implementing various structure story theories, film industries are expected to produce films with high-quality story that can be better in conveying any particular, messages.